Sperm banking and the cancer patient - Daniel H. Williams (Therapeutic Advances in Urology, 2010)
The current concepts, recommendations, and principles of sperm banking as it pertains to the comprehensive care of young men of reproductive age with cancer are reviewed. Obstacles to sperm banking are addressed as well as future directions for fertility-preserving technologies. All cancer therapies—chemotherapy, radiation, and surgery—are potential threats to a man’s reproductive potential. In addition, cancer itself can impair spermatogenesis. Thus, sperm cryopreservation prior to initiating life-saving cancer treatment offers men and their families the best chance to father biologically related children and should be offered to all men with cancer before treatment. Better patient and provider education, as well as deliberate, coordinated strategies at comprehensive cancer care centers are necessary to make fertility preservation for male cancer patients a priority during pretreatment planning.